Effect of packaging on the microbiological quality of chicken and fish viscera flour - YEHOUENOU, BONIFACE B. (My University, 2014)
Study aims on the one hand to know the microbial quality of chicken viscera, fish viscera flour and to select the packaging with the best suitable preservation condition.The flours were divided in three packages (plastic, jute bag and can) and three environments (refrigerated, ventilated, non-ventilated) for microbiological monitoring. A total of 36 samples of each flour were monitored and analyzed for two months, according to ISO and AFNOR standard methods for research of the following germs : Escherichia coli, yeasts, moulds, total and thermotolerant coliforms. The results obtained show that plastic bag and can packaging in a refrigerated or non-ventilated environments are favourable for the preservation of both flours for two months The results obtained on the production day of flours highlight the lack of germ spoilage indicator (E. coli, Staphylococcus aureus, sulphite-reducing anaerobes and coliforms). The microbial load was 2.95 and 2.84 log10 cuf/g respectively for chicken viscera and fish viscera flour.
Keywords: Chicken; viscera flour; fish viscera; flour; hygienic; quality; packaging; environment